2004
DOI: 10.1016/s0092-8674(04)00451-9
|View full text |Cite
|
Sign up to set email alerts
|

Instruction of Distinct CD4 T Helper Cell Fates by Different Notch Ligands on Antigen-Presenting Cells

Abstract: Antigen-presenting cells (APC) tailor immune responses to microbial encounters by stimulating differentiation of CD4 T cells into the Th1 and Th2 lineages. We demonstrate that APC use the Notch pathway to instruct T cell differentiation. Strikingly, of the two Notch ligand families, Delta induces Th1, while Jagged induces the alternate Th2 fate. Expression of these different Notch ligands on APC is induced by Th1- or Th2-promoting stimuli. Th2 differentiation has been considered a default process as APC-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
947
7
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 797 publications
(1,018 citation statements)
references
References 79 publications
60
947
7
4
Order By: Relevance
“…Also, a pathway involving the Notch family of ligands, which seems to be cytokine independent, has been described. Delta induces Th1 differentiation, while Jagged induces the alternate Th2 pathway [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a pathway involving the Notch family of ligands, which seems to be cytokine independent, has been described. Delta induces Th1 differentiation, while Jagged induces the alternate Th2 pathway [19].…”
Section: Discussionmentioning
confidence: 99%
“…C3H-HeJ-mice, which carry a mutation in the toll-like receptor 4 gene, Tlr4 Lps-d , may be useful to address PTX effects on the TLR4 pathway in our model. Alternatively, a model involving the Notch family with the subsequent activation of T cells has to be considered [19].…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was synthesized using Superscript III Reverse Transcriptase (Invitrogen). Quantitative expression of the Notch ligands Jagged1, Jagged2, and Delta4 was determined with a Biorad iCycler iQ (Biorad) using primers described previously [14]. Real-Time PCR was run for 40 cycles and performed in 25 mL volume containing 0.5 Â Absolute QPCR SYBR Green mix (Thermo Fisher Scientific), 1 mL of 1:10 diluted cDNA sample and 0.2 mM of each primer.…”
Section: Real-time Pcr Of Notch Ligandsmentioning
confidence: 99%
“…These include costimulatory molecules such as OX40 [12], ICOS-L [13], the Notch family member Jagged-2 [14], the cytokine IL-6 [15], or arachidonic acid metabolites such as PGE 2 [16][17][18]. Much less is known about the factors that induce such Th2-instructing DC.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies showed that Notch was also involved in mammalian differentiation processes including those governing the development of the immune system (19). The latter included evidence for a role of Notch signaling in the intrathymic differentiation of T cells (20 -22) as well as Th cell development in the periphery (23)(24)(25)(26)(27). Notch is, like TGF-␤, an evolutionarily conserved molecule but, unlike TGF-␤, is a type I transmembrane receptor rather than a receptor ligand.…”
mentioning
confidence: 99%